2017
DOI: 10.1038/srep40813
|View full text |Cite
|
Sign up to set email alerts
|

Viral microRNAs Target a Gene Network, Inhibit STAT Activation, and Suppress Interferon Responses

Abstract: Kaposi’s sarcoma-associated herpesvirus (KSHV) encodes 12 pre-microRNAs during latency that are processed to yield ~25 mature microRNAs (miRNAs). We were interested in identifying cellular networks that were targeted by KSHV-miRNAs and employed network building strategies using validated KSHV miRNA targets. Here, we report the identification of a gene network centering on the transcription factor- signal transducer and activator of transcription 3 (STAT3) that is targeted by KSHV miRNAs. KSHV miRNAs suppressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 62 publications
(86 reference statements)
3
34
0
Order By: Relevance
“…Apart from inducing STAT3 activation, KSHV can also target and inhibit STAT3 or its activators in vitro through a panel of virally encoded miRNAs. KSHV miR-K6-5, miR-K8, and miR-K9* reduce STAT3 levels, while upon IL-6 treatment, miR-K6-5 and miR-K9 decrease PKCδ and interleukin 1 receptor-associated kinase 1 (IRAK1) expression, respectively, which is accompanied by reduced p-STAT3 levels [ 102 ]. Whether in the end KSHV-induced STAT3 activation or the negative regulation of STAT3 by viral miRNAs act predominantly in endothelial cells remains unclear.…”
Section: Molecular Mechanisms Of Viral Stat3 Manipulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from inducing STAT3 activation, KSHV can also target and inhibit STAT3 or its activators in vitro through a panel of virally encoded miRNAs. KSHV miR-K6-5, miR-K8, and miR-K9* reduce STAT3 levels, while upon IL-6 treatment, miR-K6-5 and miR-K9 decrease PKCδ and interleukin 1 receptor-associated kinase 1 (IRAK1) expression, respectively, which is accompanied by reduced p-STAT3 levels [ 102 ]. Whether in the end KSHV-induced STAT3 activation or the negative regulation of STAT3 by viral miRNAs act predominantly in endothelial cells remains unclear.…”
Section: Molecular Mechanisms Of Viral Stat3 Manipulationmentioning
confidence: 99%
“…MCL1 inhibits Beclin-1, a positive regulator of autophagosome formation, to interfere with antigen processing and presentation by DCs to avoid recognition and clearance [ 89 ]. KSHV also inhibits STAT3 via the action of viral miRNAs, and by doing so it hinders the expression of ISGs such as CXCL10 , ISG15 , IFITM1 , IRF1 , OAS2 , and MX1 [ 102 ]. The vIL-10 coded by HCMV up-regulates expression of its receptor DC-SIGN in DCs, their target cells [ 81 , 111 ].…”
Section: Consequences Of Viral Perturbations In Stat3 Activitymentioning
confidence: 99%
“…They activate STAT transcription factors, which in turn induce the transcription of IFN-stimulated genes (ISGs) in infected and neighboring cells, leading to multiple antiviral functions. Diverse herpesviral miRNAs target components of the type I IFN signaling pathway, including STATs (16,17), limiting the antiviral effects of ISGs.…”
Section: Viral Mirnas and Innate Immunitymentioning
confidence: 99%
“…KSHV infection induces STAT3 phosphorylation 59 . It has been shown that inhibition of STAT3 causes KSHV reactivation 60 . We identified that PLK1 inhibition can synergize with STAT3 inhibition to efficiently reactivate latent KSHV (Fig 6), which formulates an attractive regimen for reactivating latent KSHV/EBV and eliminating KSHV/EBV-reactivated tumor cells through the viral oncolytic approach, worthy of further investigation in vivo .…”
Section: Discussionmentioning
confidence: 99%